KONSEP HATI DALAM WACANA AL-QURAN DAN AL-HADIS - Andy, Safria (Jurnal Ushuluddin, 2018)
The heart is the leader for the life of a servant. There is a period of heart leading its host to the truth and there is a period of error in every deed. The important role of the heart invites the discussion to be directed in its leadership so that the Qur'an and Hadith have a central role in its activity to direct its host.In fact, today, human life as a servant dragged down in failure, indecision and destruction in every activity he holds, so the expected social conditions do not materialize. Consequently, there has been an injustice that brings about the marginalization of the rights they should have, whether those in the lower and upper middle class economies. This is because each party claims to have done justice in fact justice for himself and the people around him and not to the people as a whole which is his duty to pay attention to it. With the explanation of the concept of heart in the discourse of Al-Quran and Al-Hadith can provide a concrete explanation to provide a clear understanding in bringing a servant to the path directed by Al-Quran and Al-Hadith.